Two New Fluorinated Phenol Derivatives Pyridine Schiff Bases: Synthesis, Spectral, Theoretical Characterization, Inclusion in Epichlorohydrin-Beta-Cyclodextrin Polymer, and Antifungal Effect - Gacitua-Santalices, M; Gacitua-Santalices, M (FRONTIERS MEDIA SA, 2018)
It has been reported that the structure of the Schiff bases is fundamental for their function in biomedical applications. Pyridine Schiff bases are characterized by the presence of a pyridine and a phenolic ring, connected by an azomethine group. In this case, the nitrogen present in the pyridine is responsible for antifungal effects, where the phenolic ring may be also participating in this bioactivity. In this study, we synthesized two new pyridine Schiff Bases: (E)-2-[(3-Amino-pyridin-4-ylimino)-methyl]-4,6-difluoro-phenol (F1) and (E)-2-[(3-Amino-pyridin-4-ylimino)-methyl]-6-fluoro-phenol (F2), which only differ in the fluorine substitutions in the phenolic ring. We fully characterized both F1 and F2 by FTIR, UV-vis, H-1; C-13; F-19-NMR, DEPT, HHCOSY, TOCSY, and cyclic voltammetry, as well as by computational studies (DFT), and NBO analysis. In addition, we assessed the antifungal activity of both F1 (two fluorine substitution at positions 4 and 6 in the phenolic ring) and F2 (one fluorine substitution at position 6 in the phenolic ring) against yeasts. We found that only F1 exerted a clear antifungal activity, showing that, for these kind of Schiff bases, the phenolic ring substitutions can modulate biological properties. In addition, we included F1 and F2 into in epichlorohydrin-beta-cyclodextrin polymer (beta CD), where the Schiff bases remained inside the beta CD as determined by the k(i), TGA, DSC, and S-BET. We found that the inclusion in beta CD improved the solubility in aqueous media and the antifungal activity of both F1 and F2, revealing antimicrobial effects normally hidden by the presence of common solvents (e.g , DMSO) with some cellular inhibitory activity. The study of structural prerequisites for antimicrobial activity, and the inclusion in polymers to improve solubility, is important for the design of new drugs.